EKSPLORASI BAKTERI ENDOFIT PADA TANAMAN SAMAMA (Anthocephallus macrophyllus ) - Mendez, Syeren; Matinahoru, Johan; Hadijah, Miranda (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
Bacterial exploration aims to find out how endophytic bacteria associate with the roots of samama plants and find out the morphological characteristics of the endophytic bacteria found. So we can determine the type/family of endophytic bacteria on the Samama plant. Sampling of samama plants (Anthocepalus macropyllus) was taken on the campus of the Faculty of Agriculture, Pattimura University. The parts of the plant samples taken were roots, bark, leaf twigs and leaves. The number of tree samples taken as examples was 3 individual trees. Each plant organ sampled is 200 gr. The data analysis method used is by adjusting the data resulting from the identification of macroscopic and microscopic characteristics with the characteristics of bacterial families that are available according to references. Based on the results of this research, it can be concluded that: there are 9 isolates of endophytic bacteria, namely KB1 KB2 KB3 KB4 A1 A2 A3 A4 and B1 in the root, stem and bark tissues of Samama plants. Endophytic bacterial isolates Kb1, Kb2, kb3, kb4, A2, A4 have similar characteristics to the bacterial group of the genus Bacillus with the characteristics of rod-shaped cells and are classified as gram positive, while isolates Kb4, A2 and A4 have the characteristics of the genus Bacillus and have rod-shaped characteristics and classified as gram negative. Then isolate A1, A3, B1. It has similar characters to members of the coccus genus, namely round cells and is classified as gram positive, but the isolate code is classified as gram negative. The results of biochemical analysis show that samama plants have 3 types of bacteria, namely Bacillus altitudinis, Bacillus pumilus and Bradyrhizobium sp.